Room temperature magnetic graphene oxide- iron oxide nanocomposite based magnetoresistive random access memory devices via spin-dependent trapping of electrons - Lin, Aigu L. (2014)
A MRAM device is fabricated using magnetic graphene oxide- iron oxide nanoparticles nanocomposites together with a platinum electrode and a ferromagnetic cobalt electrode. The device allow for a positive magnetoresistance up to 280% via the spin-dependent trapping of charge carriers. Its low resistance state can be restored by releasing the trapped charges by reversing the direction of current flow together with the magnetic field orientation.